Fenomena Hijrah Mahasiswi Universitas Mataram Dalam Perspektif Konstruksi Sosial Peter L Barger dan Thomas Luckmann - Supadmi, Ni Wayan (Madania: Jurnal Ilmu-Ilmu Keislaman, 2024)
Hijrah is a contemporary Islamic religious phenomenon in Indonesia, especially in urban areas. Not only artists, but the phenomenon of migration has begun to spread to the campus world. As a result, this paper aims to investigate the phenomenon of student migration at Mataram University in Peter L. Berger and Thomas Luckmann's social construction. This study falls under the category of field research. We obtained primary data from Mataram University students who are still active and have migrated. Six students met the criteria for the selection of respondents in this study. The secondary data include various books, media, and journal articles that can support this research. Data collection methods include interviews and observations. Following the collection of data, an analysis was carried out using the Miles and Hubarman models. The study's results illustrate the phenomenon of students at Mataram University migrating within the social construction of Peter Berger and Thomas Luckmann, utilizing three dialectical moments. Initially, the term "externalization" refers to the process by which students acquire knowledge about migration from their peers on campus and lectures given by ustaz Hanan Attaki and Adi Hidayat via various media platforms such as Facebook, Instagram, Tik Tok, and others. Next, the students joined the Baabul Hikmah Campus Da'wah Institute's Student Activities Unit. IIn this institution, they connect with individuals who share a common understanding and receive support to maintain consistency in their emigration process. he last phase is known as internalization, where the students comprehend that their migration signifies a positive shift. Hijrah begins with a strong will and determination to change, trying to abandon undesirable habits, speaking politely, dressing in secret, and not dating to avoid undesirable things.